Harry Channell interviewed by John Meredith for the John Meredith folklore collection - Channell, Harry, 1903-; Meredith, John, 1920-2001. (1983)
Folkloric recording. Harry Channell describes and remembers Bush xylophone.
Recorded by John Meredith at Cawdor, N.S.W., in December 1983.
Also available online
Keywords: Channell, Harry, -- 1903- -- Interviews; Folk music -- Australia; Xylophone music